Write better English - Ward, J. (Cambridge [Cambridgeshire] ; New York : Cambridge University Press, 1984)
Teaches English writing skills by approaching English as a foreign language, emphasizing sentence structure, connecting concepts and good style. Includes exercises.
Includes indexes.
Keywords: English language -- Textbooks for foreign speakers; English language -- Composition and exercises -- Juvenile literature; English language -- Composition and exercises; English language -- Textbooks for foreign speakers